Evaluation and Analysis of the Rational Structure of Sources for Assets Formation - Kharabadze, Elene; Jikia, Merab (Archives of Business Research, 2018)
The most important issue in analyzing financial sustainability is the assessment of the rationality of the balance of equity and debt capital. The structure of the sources of a company’s assets is assessed both by internal and external users of the information. When analyzing financial sustainability, the asset turnover rate should be necessarily considered. The enterprise with higher asset turnover rate may have a higher share of borrowed sources in total liabilities, so that it does not endanger its solvency and the risk of creditors does not increase (an enterprise having high capital turnover rate easily ensures the inflow of cash resources and as a result, payments on the liabilities); therefore, such enterprises are more attractive to creditors and lenders. Final conclusions regarding the rationality of the structure of liabilities in the enterprise can be made based on complex analysis of the factors, which will include the specificity of the sector, speed of asset turnover, profitability, etc.